EXPLORING PERCEPTIONS OF STUDENTS AND TEACHERS TOWARDS CODE-SWITCHING AT INTERMEDIATE LEVEL IN PAKISTAN - Madiha Rehman; Youmna Rehman (Universitas PGRI Madiun, 2021)
This research study concentrates on the insight of students & teachers about code-switching at the intermediate level in Pakistan. It is evident that Pakistani classrooms are culturally diverse & teachers used to practice from one language to another to enable their students to stand on their toes. This research corroborated through the qualitative method that code-switching is an ultra-practical technique for mixed ability students at intermediate level. Code-switching not only takes place among students but also among educators to unclog the learning process. Nonetheless, not many have looked at it from the students' perspective in response to what they think about their teacher’s code-switching in Pakistan. Therefore, the researcher took this opportunity to look into pupils' insight about code-switching. The semi- structured interview was collected from five intermediate students & five lecturers of a well-known private college in Karachi, Pakistan. The findings of the study indicate that students show a keen interest in learning the concepts when the teacher does code-switching during his lecture. Thus, this study suggests that code-switching is an effective teaching strategy when teaching intermediate students in Pakistani scenarios.